Otomasi Greenhouse Berbasis Mikrokomputer RASPBERRY PI - Adi Fajaryanto Cobantoro; Mohammad Bhanu Setyawan; Miftahudin Agung Budi Wibowo (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2019)
The entry of the industrial revolution era, many occur anthropogenic. One of the causes of ecological imbalances is the lack of reforestation in urban environments. Environmental conditions are the main thing to achieve production. The main factors that influence plant growth and development are temperature and humidity, in this case to reach the desired temperature and humidity is very difficult and difficult to control as needed. As if the temperature and humidity limit agricultural production. From the existing problems, building a greenhouse prototype can automatically control temperature and humidity according to the actual conditions in the plant. To achieve this condition use a control system that controls temperature and humidity automatically. The system works according to the value that has been determined then the value compared with the DHT22 sensor to measure air humidity and YL-69 as a controller of soil moisture and as a controller for watering plants automatically. The prototype testing was done using a computer and raspberry pi microcontroller by connecting the UTP cable to the raspberry pi to the laptop with an internet sharing connection. The prototype can run and can be controlled by telegram.